2006
DOI: 10.1152/ajpregu.00345.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids act in the dorsal hindbrain to modulate baroreflex control of heart rate

Abstract: Bechtold, Andrea G., and Deborah A. Scheuer. Glucocorticoids act in the dorsal hindbrain to modulate baroreflex control of heart rate. Am J Physiol Regul Integr Comp Physiol 290: R1003-R1011, 2006. First published November 3, 2005 doi:10.1152/ajpregu.00345.2005.-Systemic corticosterone (Cort) modulates arterial baroreflex control of both heart rate and renal sympathetic nerve activity. Because baroreceptor afferents terminate in the dorsal hindbrain (DHB), an area with dense corticosteroid receptor expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 57 publications
(105 reference statements)
2
28
1
Order By: Relevance
“…These studies indicated that higher doses of Cort administered intracerebroventricularly produce small increases in baseline arterial pressure, whereas low doses were without effect. 26 -28 We reported previously that DHB Cort pellets increased baseline arterial pressure by 5 to 6 mm Hg after 4 days of treatment, 7,15 although in the present study there were no differences in baseline arterial pressure between groups. This was not because of a difference in duration of DHB Cort treatment, because baseline arterial pressures in rats treated with DHB Cort for 4 days (105Ϯ4 mm Hg, nϭ8) or 6 days (104Ϯ3 mm Hg, nϭ7) were not different.…”
Section: Effect Of Cort On Baseline Arterial Pressurementioning
confidence: 47%
See 3 more Smart Citations
“…These studies indicated that higher doses of Cort administered intracerebroventricularly produce small increases in baseline arterial pressure, whereas low doses were without effect. 26 -28 We reported previously that DHB Cort pellets increased baseline arterial pressure by 5 to 6 mm Hg after 4 days of treatment, 7,15 although in the present study there were no differences in baseline arterial pressure between groups. This was not because of a difference in duration of DHB Cort treatment, because baseline arterial pressures in rats treated with DHB Cort for 4 days (105Ϯ4 mm Hg, nϭ8) or 6 days (104Ϯ3 mm Hg, nϭ7) were not different.…”
Section: Effect Of Cort On Baseline Arterial Pressurementioning
confidence: 47%
“…In a recent study, we reported that DHB Cort treatment attenuated the gain and increased the midpoint of the arterial baroreceptor reflex. 7 Thus, it is possible that attenuation in baroreflex control of sympathetic nerve activity contributed to the effect of DHB Cort to enhance the arterial pressure response to stress observed in this study. However, if there was enhanced activation of the sympathetic nervous system, it was not universal, because the heart rate response to stress was not elevated in the DHB Cort rats.…”
Section: Mechanism Of Cort Actionmentioning
confidence: 77%
See 2 more Smart Citations
“…18 Glucocorticoids also act within the brain to regulate the baroreflex function and thereby influence sympathetic tone. 19 The mineralocorticoid receptor could also have contributed to hypertension in our patient. In cases of cortisol excess, the main agonist of the receptor may be cortisol rather than aldosterone.…”
Section: How Do Acth and Glucocorticoidsmentioning
confidence: 70%